ANALISIS PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN BUS TRANS JOGJA (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2024)
This research discusses public transportation, namely the Trans Jogja Bus with the aim of analyzing the influence of service quality and trust on customer loyalty of the Trans Jogja Bus. This research uses quantitative methods in the form of filling out questionnaires carried out in Yogyakarta accompanied by the use of analytical tests in the research. The population used was all loyal Trans Jogja Bus users with a sample of 30 respondents who were determined non-probably and measured using a purposive sampling technique. This research has important benefits for Trans Jogja Bus management, namely helping them to improve service quality and increasing customer trust through customer loyalty. The results of this research hypothesis test show that service quality has a negative and insignificant effect on customer loyalty, the results of trust show a positive and significant effect on customer loyalty, while service quality and trust have a positive and significant effect on customer loyalty.
Keywords: service quality; trust, loyalty; customers; Trans Jogja Buses